Intervention program for the improvement of attention abilities in Argentinean school children - Mirta Susana Ison (Universidad de San Buenaventura, 2011)
We understand attention as an active and constructive mechanism that can be improved with regular practice. The purpose of the present research was to evaluate the efficiency of an intervention program aimed at stimulating attention abilities in Argentinean school children between 7-12 years old previously detected as having low attention efficiency, and considering age and sex. We formed two groups: a) under study, with 72 students, and b) control, with 66 students. In the post-intervention stage the results showed a statistically significant increase of attention efficiency in the children involved in the program. These are promising results regarding their application to different cognitive performance profiles and the various development contexts.